2023
DOI: 10.1021/acsnano.2c12698
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like Nanozyme with Highly Porous Carbon Matrix Induces Robust Oxidative Storm against Drug-Resistant Cancer

Abstract: Reactive oxygen species (ROS) generators are sparking breakthroughs in sensitization and treatment of therapy-resistant tumors, yet the efficacy is drastically compromised by limited substrate concentrations, short lifetimes of free radicals, and restricted oxidative damage. Herein, a flower-like nanozyme with highly permeable leaflets accommodating catalytic metal sites was developed to address the challenges by boosting substrate and product accessibility. In the formation of a zeolite imidazole framework, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The increased ratio of Bax/Bcl‐2 indicated that the PdCu NYs promoted apoptosis. [ 36 ] Moreover, after treatment with PdCu upon 1064 nm laser irradiation, the expression levels of caspase‐3 and caspase‐9's activated form (cleaved caspase‐3 and cleaved caspase‐9) were upregulated with a greater extent. Noteworthy, the colony efficiency assay demonstrated a superior therapeutic efficacy of PdCu+Laser group in comparison to the other groups Figure 3i, which is consistent with the above results.…”
Section: Resultsmentioning
confidence: 99%
“…The increased ratio of Bax/Bcl‐2 indicated that the PdCu NYs promoted apoptosis. [ 36 ] Moreover, after treatment with PdCu upon 1064 nm laser irradiation, the expression levels of caspase‐3 and caspase‐9's activated form (cleaved caspase‐3 and cleaved caspase‐9) were upregulated with a greater extent. Noteworthy, the colony efficiency assay demonstrated a superior therapeutic efficacy of PdCu+Laser group in comparison to the other groups Figure 3i, which is consistent with the above results.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it has been demonstrated that Co is capable of deforming the cell membrane structure of bacteria and has the potential to confer enzyme-like activities. 30,31 Co single-atom nanozymes have been confirmed to derive their oxidase-like activity 32 and POD-like activity 33 from the active site of Co–N coordination. Using a transition metal compound as one of the precursors is the most common way of synthesizing nanozymes.…”
Section: Introductionmentioning
confidence: 92%
“…One can envision that precise drug administration can be achieved when drugs are loaded onto the SAzymes for targeted transport to the cancer sites. 176 In conclusion, targeted tumor therapy has remained a key clinical challenge, and SAzymes have emerged as a unique platform, which demands further and more thorough studies.…”
Section: Cancer Diagnosis and Therapymentioning
confidence: 99%